The group embedded figure and pattern test for cognitive styles of deaf-mute students - Vaula Greennita Kusumawati; Andriyani Andriyani (Universitas Ahmad Dahlan, 2021)
This research aim is to describe deaf-mute students' cognitive style which seen in the condition of the Group Embedded Figure Test (GEFT). Data was collected through given by GEFT to four deaf-mute students of SLBN 2 Bantul and the data were analyzed through an interactive analysis of the Miles & Huberman model namely data collection, data reduction, data display, verification or conclusion inferred. From the test results, two students were categorized to Field-Dependent (FD) cognitive style and the other students were categorized to Field-Independent (FI) cognitive style. Students with FD cognitive styles tend to have difficulty focusing on something or analyzing the pattern into different parts. In contrary, students with FI cognitive style are more capable to accept separate parts of an overall pattern and analyzing the pattern into its components.